PENGARUH PHILANTHROPY DISCLOSURE PADA NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Dewi, Dewa Ayu Anggi Isyana; Damayanthi, I Gst Ayu Eka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
Firm value represents investors view of a enterprise's success as reflected through the stock price formed from economic, social, and environmental aspects. Most companies are only concerned with economic aspects without prioritizing social and environmental aspects. This study was lead to empirically investigate the impact of philanthropy disclosure on firm value, considering firm size as moderating variable. This research utilizies data from mining companies listed on the Indonesia Stock Exchange between 2020 and 2022. A total of 59 enterprises, comprising 177 observations, were selected as samples through purposive sampling techniques. Data analysis was executed through the Absolute Difference Value Test using the Eviews application. This study found philanthropy disclosure positively and significantly affects firm value. Additionally, the impact of philanthropy disclosure on firm value can be amplified by firm size. The study’s implications demonstrate the application of signal theory and provide benefits to interested parties, especially companies and investors related to philanthropy disclosure and firm size that can increase firm value.